Non-commercial clinical trials of a medicinal product: can they survive the current process of research approvals in the UK?. Issue 7 (30th June 2006) - Sheard, L; Tompkins, C N E; Wright, N M J; Adams, C E
Abstract : Over recent years, considerable attention has been paid to the National Health Service (NHS) research governance and ethics approvals process in the UK. New regulations mean that approval from the Medicines and Healthcare Products Regulatory Agency (MHRA) is now also needed for conducting all clinical trials. Practical experience of gaining MHRA and sponsorship approval has yet to be described and critically explored in the literature. Our experience, from start to finish, of applying for these four approvals for a multicentre randomised controlled trial of two licensed drugs for opiate detoxification in the prison setting is described here. In addition, the implications of the approvals process for research projects, particularly clinical trials, in terms of time and funding, and also indirect implications for NHS patients are discussed. Inconsistencies are discussed and suggestions that could improve and streamline the overall process are made. The current approvals process could now be hindering non-commercial clinical trials, leading to a loss of important evidence-based medical information.